PICTURE OF PERINEAL WOUND HEALING IN Mrs. I POST PARTUM BY GIVING BETEL LEAF BOILED WATER IN KAJONGAN VILLAGE, PURBALINGGA - Teti Sundari; Priyatin Sulistyowati; Wiwik Priyatin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Healing perineal wounds in postpartum mothers is an essential aspect of recovery after childbirth. These wounds can cause discomfort and potentially disrupt daily activities as well as the mental health of the mother. The presence of perineal wounds may lead to infection; Therefore, wound care is necessary to reduce the risk of infection and accelerate the healing process. Betel leaves are known for their antiseptic and anti-inflammatory properties that can support the healing process. Objective: This study aims to describe the healing of perineal wounds in postpartum mothers with the administration of betel leaf decoction. Method: This research employs a qualitative descriptive method with a case study approach. Results: After implementing perineal care using betel leaf decoction, which was applied regularly in the morning and evening after bathing for 5 days, there was a noticeable acceleration in the healing process of the wounds and an increase in maternal satisfaction regarding wound care. Conclusion: Wound care for perineal injuries using betel leaf decoction is effective for healing perineal wounds in postpartum mothers .